MINAT SISWA TERHADAP SENI TARI DALAM KEGIATAN PENGEMBANGAN DIRI DI SMP N 1 TEMPULING DESA SUNGAI SALAK KECAMATAN TEMPULING RIAU - Helfira Helfira; Fuji Astuti; Indrayuda Indrayuda (SENDRATASIK UNP, 2017)
AbstractThis research aims at finding out and describing students interests in danding, one of the extracurricular activities offered at SMPN 1 Tempuling Desa Sungai Salak Kecamatan Tempuling Riau. Descriptive approach was applied in this qualitative study. The objects were 15 students of the dancing class. Data were obtained from documentation, interview, and observation. They were analyzed by using the presentation analysis technique as proposed by Sudjana.This research was conducted on November-Desember of 2016. From the observation of the students activity, 3 indicators were used. They were willingness, attention, and participation. The instrument included 6 statements about the students willingness, 9 statements related to their attention, and 5 statements about their participation. Whether they did or not do what was described in the statement was analyzed in this research. The research result shows that from meeting I to meeting VI, the students score was 51,9 %. It is the average category.Keywords: interest, dance, extracurricular